SUSTAINABLE AND SMART CITIES: CONVERGENCES, CHALLENGES AND GAPS IN GLOBAL SCIENTIFIC PRODUCTION - Lins, Igor Augusto de Andrade; Alves, José Luiz (Seven Editora, 2025)
This article presents a systematic review of the literature on sustainable and smart cities, aiming to identify the main challenges and approaches addressed in scientific production between 2017 and 2025. Thirty articles indexed in the Web of Science database were analyzed, supported by thematic and bibliometric analysis. The results reveal a growing convergence between the paradigms of urban sustainability and technological innovation, but also highlight significant barriers to their implementation, especially in contexts of the Global South. Among the main obstacles are the fragmentation of indicators, institutional disarticulation, governance limitations, and the risk of exclusionary technocentric approaches. The analysis highlights the need for integrated strategies that articulate citizen participation, social equity, and the ethical use of technology. The study offers theoretical and practical insights for researchers, policymakers, and urban managers committed to more just, resilient, and sustainable cities.DOI: https://doi.org/10.56238/sevened2025.029-035